Penilaian Hasil Belajar Bagi Anak Berkebutuhan Khusus Dalam Praktik Pendidikan Inklusif - Putri Zalika Wulandari; Habib Nugraha Putra; Umi Rohimah; Hendri Marhadi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Learning outcomes assessment is a process that involves measuring and assessing students' knowledge, skills and attitudes towards established standards. Assessment of learning outcomes for children with special needs (ABK) must be carried out with adjustments to the student's abilities, such as vision, hearing, intellectual and physical abilities. This research aims to describe the assessment of learning outcomes for ABK in inclusion classes. The research method used is a literature review. The results of this research are that there are several types of assessment that can be used for inclusive education, namely formative assessment, summative assessment, diagnostic assessment, affective assessment, and fortopolio assessment. Inclusive education assessment is the process of measuring and assessing the achievements of children with special needs (ABK) in learning. The aim of assessment in inclusive education is to obtain information about students. This information can be used to help schools and teachers make decisions about instruction, learning outcomes, diagnosis, and educational improvement for each student.